Implementasi Pembelajaran Aquatik dalam Pendidikan Jasmani di SMP Prima Cendekia Islamic - Dimas Hot Asi Pasaribu; Carsiwan; Oktoviana Nur Ajid (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to examine the implementation of aquatic learning and identify the factors that hinder swimming instruction at SMP Prima Cendekia Islamic. The study employed a qualitative approach using a phenomenological method. The research informants consisted of the Vice Principal for Curriculum, a Physical Education teacher, and one student selected through purposive sampling. Data were collected through triangulation of interviews, observations, and documentation. The findings revealed that the implementation of aquatic learning had been carried out effectively through the stages of planning, implementation, and evaluation. Learning activities were conducted through practical sessions in a swimming pool using demonstration and direct practice methods, enabling students to master basic swimming techniques while enhancing their confidence and courage. The main obstacles identified included limited instructional time, financial constraints, differences in students' initial swimming abilities, and fear of water activities. Nevertheless, these challenges were addressed through teacher guidance and support from the school, allowing aquatic learning to be implemented effectively. Keywords: Learning Implementation, Aquatic Learning, Swimming, Physical Education